TECHNIQUE OF ESTIMATE OF CONDUCTIVITY OF SMALL COAL SAMPLES BY THEIR INFLUENCE ON SIGNAL OF SPIN-LABEL IN RESONATOR OF ESR SPECTROMETER - N. A. Poklonski; S. A. Vyrko; O. N. Poklonskaya; N. I. Gorbachuk; A. I. Siahlo (Приборы и методы измерений, 2015)
The results of study at room temperature in the air of influences of the nonresonant absorption of microwave electromagnetic radiation by coal samples of different masses in the center of H102-resonator on the electron spin resonance (ESR) signal of a standard sample (spin label) of a ruby crystal, permanently mounted on the side wall of the resonator, are presented. Quantitative evaluation of the microwave conductivity of the studied coal samples based on the ESR measurements of ruby are made. Results can be applied for monitoring of electrical parameters of coals in the microwave range.